Developing valid and practical PISA-like mathematical literacy tasks based on the ethnomathematics of small border islands - Rupilele, Karolina; Sugiarto, Sigit; MA, Ratnah Kurniati (Indonesian Journal of Science and Mathematics Education, 2026)
Mathematical literacy remains a major challenge for Indonesian students, particularly in remote and small border island regions where learning resources are often disconnected from students’ cultural experiences. To address this issue, this study aimed to develop a PISA-like mathematical literacy assessment instrument based on the ethnomathematics of small border islands and examine its potential effects on students’ mathematical literacy skills. This study employed a design research approach involving 57 junior secondary school students from Moa Island, Southwest Maluku, Indonesia. Data were collected through documentation, interviews, walkthroughs, and students’ written responses. The developed tasks integrated local cultural contexts, including Koli leaf weaving, Lutur Batu, the Kisar Pyramid, and the Nahuwook tradition. The results showed that the tasks met the criteria of validity and practicality. Field-test findings revealed that students generally performed well on Level 3 and Level 4 tasks but had difficulty with Level 5 and Level 6 tasks, indicating limited ability to demonstrate higher-order mathematical literacy skills. These findings suggest that culturally relevant contexts can support students in understanding and applying mathematics in meaningful situations. This study contributes to the literature by introducing ethnomathematical contexts from small border islands as a novel source for developing culturally responsive PISA-like mathematical literacy tasks and assessment resources.